Use the quadratic formula.
![x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/rxvf73usjbbwyik14knxdemoz21vfz2ufc.png)
Where a = 3, b = -31, and c = -60.
![x=\frac{-(-31)\pm\sqrt[]{(-31)^2-4(3)(-60)}}{2(3)}](https://img.qammunity.org/2023/formulas/mathematics/college/lm0ja7rwipw9rvczpavu4nxiyl26unh1j2.png)
Solve to find both solutions.
![x=\frac{31\pm\sqrt[]{961+720}}{6}=\frac{31\pm\sqrt[]{1681}}{6}=(31\pm41)/(6)](https://img.qammunity.org/2023/formulas/mathematics/college/rt9rnytlo2d1xjrtr8a59a58ppw2qxklpl.png)
Rewrite the expression as two.
![\begin{gathered} x_1=(31+41)/(6)=(72)/(6)=12 \\ x_2=(31-41)/(6)=(-10)/(6)=-(5)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qiu3kfhmiwoa2cgvdswvunm47vnz7xbhds.png)
Once we have the solutions, we express them as factors. To do that, we have to move the constant to the right side of each equation.
![\begin{gathered} x=12\to(x-12) \\ x=-(5)/(3)\to(3x+5)_{} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ymmolxt5hy62t3gce8umgpkvp9i8eu77yo.png)
As can observe, the factor of the polynomial is (x-12).
Therefore, the answer is d.